Optimalisasi Instagram Untuk Umkm Croffle Tos: Strategi Promosi Untuk Menarik Pelanggan - Ikram, Muhammad; Fadillah, Dani (Borobudur Communication Review, 2024)
Small and medium enterprises (SMEs) face significant challenges as they navigate an increasingly competitive market. One effective strategy to enhance competitiveness is the use of social media, particularly Instagram. Croffle TOS, a snack business specializing in Croffle and Toast, established in 2021 in Umpur Harjo, remains relatively unknown to the public. This study aims to assist in the business development of Croffle TOS through digital marketing on Instagram by strengthening brand profiles, creating engaging taglines, and implementing promotional mix strategies. The analysis reveals that the lack of promotion on Instagram is a major obstacle in increasing brand awareness. By applying appropriate promotional strategies, such as attractive banners, engaging posts, and targeted consumer segmentation, it is expected to boost sales and expand brand recognition.